Systems View of Deconditioning During Spaceflight Simulation in the PlanHab Project: The Departure of Urine 1 H-NMR Metabolomes From Healthy State in Young Males Subjected to Bedrest Inactivity and Hypoxia - Šket, Robert; Deutsch, Leon; Prevoršek, Zala; Mekjavić, Igor B.; Plavec, Janez; Rittweger, Joern; Debevec, Tadej; Eiken, Ola; Stres, Blaz (Frontiers in Physiology, 2020)
Little is known about the two faceted nature of spaceflight, where human physiological responses are coupled to microbial responses to inactivity on one side and prolonged confination within built environment, similar to hospital settings, on the other. The PlanHab project was designed to investigate in a controlled manner the combined effects of prolonged inactivity/unloading and hypoxia on a medically pre-screened cohort of healthy male volunteers in cross-over design. In total, 523 urine metabolomes were analyzed and processed using standard quantitative approaches and ensemble of multivariate methods from three interventions: normoxic bedrest, hypoxic bedrest and hypoxic ambulation. Results show that in contrast to hypoxic ambulation and run-in period inactivity alone or combined with hypoxia resulted in significantly reduced systemic metabolic diversity, increasing number of affected metabolic pathways and faster deconditioning. The maintained vertical posture and controlled but limited activity in hypoxic ambulation variant prevented the development of negative physiological symptoms such as insulin resistance, low level systemic inflammation, constipation, depression, symptoms of metabolic syndrome and body deconditioning reported before in the PlanHab project. Metabolic and pathway diversity are apparently required to prevent the negative spiral between the host and microbiome physiology governed by intestinal environment and proinflammatory immune activities of the host in response to physical inactivity.